Respostas
respondido por:
3
Equação: (x – a)² + (y – b)² = r²
a= -5
b= 2
r= 3
Substituindo:
(x + 5)² + (y – 2)² = 9
a= -5
b= 2
r= 3
Substituindo:
(x + 5)² + (y – 2)² = 9
hcsmalves:
Retifique sua resposta, Coralinex.
respondido por:
1
C(-5, 2) e r = 6/2 => r = 3
Equação reduzida da circunferência
(x - a)² + (y - b)² = r²
[x - (-5)]² + (y - 2)² = 3²
(x + 5)² + (y - 2)² = 9
Equação reduzida da circunferência
(x - a)² + (y - b)² = r²
[x - (-5)]² + (y - 2)² = 3²
(x + 5)² + (y - 2)² = 9
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás